Carbon impurity-free, novel Mn, N co-doped porous Mo2C nanorods for an efficient and stable hydrogen evolution reaction. Issue 9 (6th August 2019) - Zhou, Yajun; Xu, Jieyu; Lian, Cheng; Ge, Lin; Zhang, Lingxia; Li, Liang; Li, Yunheng; Wang, Min; Liu, Honglai; Li, Yongsheng
Abstract : Carbon impurity-free, novel Mn, N co-doped porous Mo2 C nanorods reduce the hydrogen adsorption energy, functioning as efficient HER electrocatalysts. Abstract : Heteroatom doping is an effective way to modulate the electronic configuration and optimize the electroactivity over a series of electrocatalytic materials. Here we report novel kinds of Mn, N co-doped porous Mo2 C nanorods for the hydrogen evolution reaction (HER) in acidic solution, which are facilely fabricated based on Mn-modified MoO x -amine precursors. The obtained porous, monocrystalline nanorods without carbon impurities could not only provide abundant catalytic sites, but also facilitate electrolyte penetration and hydrogen release. Furthermore, the fine-tuned electronic structure of Mo2 C nanorods with Mn, N dopants could produce more available active sites and reduce the hydrogen adsorption energy (Δ G H* ). As a result, the optimized Mn, N co-doped Mo2 C nanorods exhibit high HER activity with a low overpotential ( η 10 = 163 mV), a small Tafel slope (66 mV dec −1 ), and excellent long-term stability in acidic electrolyte. EPR and DFT calculations confirm that the high performance originates from new active sites (Mn site), a low charge-transfer resistance and an optimized adsorption–desorption behavior after Mn, N co-doping. This work may provide a new pathway to design and explore efficient non-noble metal water-splitting electrocatalysts via electronic engineering of their compositions and nanostructures.